A comparison of virus concentration methods for molecular detection and characterization of rotavirus in bivalve shellfish species. (April 2015) - Kittigul, Leera; Singhaboot, Yutatirat; Chavalitshewinkoon-Petmitr, Porntip; Pombubpa, Kannika; Hirunpetcharat, Chakrit
Abstract: The objectives of this study were to develop a method for concentrating rotavirus, to assess the detection rate, and to characterize the genotype of naturally occurring rotavirus in bivalve shellfish species; including oysters ( Saccostrea forskali ), cockles ( Anadara nodifera ), and mussels ( Perna viridis ). The results demonstrated that an adsorption-twice elution-extraction method was less-time consuming method of concentrating the spiked rotavirus, yielding high sensitivity of 1.14 genome copies/g of digestive tissues from all three shellfish species, as detected using an RT-nested PCR. In seeding experiments, rotavirus as low as 1.39 genome copies was able to be detected in 4 g of digestive tissues or per sample. In the period of August 2011 to July 2012, of the 300 bivalve shellfish samples collected and tested, 24 (8.0%) were found to be contaminated with rotavirus, the figures being: oysters, 13/100 samples; mussels, 10/100 samples; and cockles, 1/100 samples. By DNA sequencing of the RT-nested PCR products and phylogenetic analysis, the rotaviruses detected were classified into G1, lineage II (4 samples); G3 (10 samples): lineage I (3 samples), lineage IIIc (3 samples), lineage IIId (3 samples), lineage IV (1 sample); G9 (6 samples); and G12, lineage III (1 sample). These findings suggest that this virus concentration method provides high sensitivity for the detection of rotavirus from the three bivalve shellfish species. The prevalence of rotavirus and the identified genotypes contribute to the molecular epidemiology of rotavirus in different shellfish species. Highlights: Three methods were evaluated for rotavirus extraction from bivalve shellfish. A developed method provided high sensitivity for detection of rotavirus in shellfish. Naturally occurring rotaviruses were detected in oysters, cockles, and mussels. Rotavirus G3 genotype present in cockles and G12 in mussels are first described.